Environmental lead poisoning among children in Porto Alegre state, Southern Brazil - Mariana Maleronka Ferron; André Klafke de Lima; Paulo Hilário Nascimento Saldiva; Nelson Gouveia
OBJECTIVE: To estimate the prevalence of lead poisoning in children and to identify associated factors, as well as possible local sources of contamination. METHODS: A cross-sectional prevalence study conducted in 2006 with a random sample of 97 children age zero to five years from a neighborhood in Porto Alegre, Southern Brazil. Blood lead levels were measured and a questionnaire administered to collect information on sociodemographics, recycling and dwelling. A preliminary environmental evaluation was carried out with direct analysis of soil and indirect analysis of air pollution with bioindicators to identify possible sources of contamination. To analyze lead concentrations from the different collection sites, for each type of material studied, ANOVA was performed with a Brown-Forsythe adjustment for heteroscedasticity and with Dunnett's T3 procedure for multiple comparisons of unequal variances. RESULTS: Blood lead levels > 10.0 µg/dL was found in 16.5% of children. Recycling of waste at home, low father's education level, and increased age of children were associated with increase blood lead levels. High lead levels were found in soil, and there was little indication of lead air pollution. CONCLUSIONS: A high prevalence of lead poisoning was identified, and the potential sources of contamination in this community appear related to waste recylcing activities. Studies should be conducted with other populations of Brazilian children and evaluate potential sources of local and general contamination, to accurately characterize this issue in Brazil.